Unveiling scientific communities about sustainability and innovation. A bibliometric journey around sustainable terms. (20th July 2016) - Franceschini, Simone; Faria, Lourenço G.D.; Jurowetzki, Roman
Abstract: Literature about the relationship between innovation and sustainability has skyrocketed in the last two decades and new terms have appeared. However, only very few bibliometric analyses have reviewed some of these terms ( eco-innovation, environmental innovation, green innovation, and sustainable innovation ), and they concluded that such terms are mostly interchangeable. These findings surprise in light of the different positions shown in the innovation for sustainability debate. Our bibliometric analysis tracks meanings and communities associated with these four terms and indicates some overlaps, especially between eco-innovation and environmental innovation . However, we found relevant differences of meanings and communities that reflect the different positions in the innovation for sustainability debate.